A Most Splendid Company : The Coronado Expedition in Global Perspective - Flint, Richard, 1946-; Flint, Shirley Cushing (Book collections on Project MUSE., 2019)
This magisterial volume unveils Richard and Shirley Flint's deep research into the Latin American and Spanish archives in an effort to track down the history of the participants who came north with the Coronado expedition in 1540. Through their investigation into thousands of legal cases, financial records, proofs of service, letters, journals, and other primary materials, they provide social and cultural documentation on the backgrounds of hundreds of individuals who made up the Coronado expedition and show that the expedition was the first phase of a three-phase effort to complete the Columbian project: to delineate a westward route to Asia from Spain.